Design, synthesis and anticancer activity of Novel benzimidazole containing quinoline hybrids - Shashidhar Bharadwaj Srinivasa; Boja Poojary; Bhuvanesh Sukhlal Kalal; Usha Brahmavara; Dhanashri Vaishali; Anupam J. Das; Thobias Mwalingo Kalenga; Maruthibabu Paidikondala; Madan Kumar Shankar (Results in Chemistry, 2024)
In this work we present the synthesis of benzimidazole-quinoline hybrids series (9a-c and 10a-f), characterized using spectroscopy studies (FT-IR, 1H NMR, and mass spectroscopy). The precursor for the hybrid compounds consists of two schemes: i. synthesis of substituted quinoline-4-carboxylic acids (3a-b) with various acetophenones. ii. The key intermediates (8a-c) were obtained initially from the benzimidazole-5-carboxylates (7a-c), were efficiently synthesized by ‘one pot’ nitro reductive cyclization reaction between ethyl 3-nitro-4-(substituted amino) benzoates 6a-c and 5-bromothiophene-2-carbaldehyde. iii. Further, the benzimidazole esters (7a-c) were converted into the corresponding hydrazides (8a-c) and then finally obtained the benzimidazole-quinoline hybrids series (9a-c and 10a-f). Compounds 7a and 7b were crystallized and their molecular structures were determined using a single crystal X-ray diffraction method. The resultant compounds from the synthesis were screened (in-silico and in-vitro) for their anti-cancer activities (human melanoma cell line (A375) and human breast cancer cell line (MDA-MB-231)). The p53 receptor protein was used for the molecular docking analysis and compound (name) 10b binds the target site with four hydrogen bonds (−6.25 Kcal/mol). The antioxidant activity revealed compounds 9a (IC50 = 604.8 μg/mL) and 9b (IC50 = 604.8 μg/mL 683.7 μg/mL) to exhibit the highest percentage of inhibition and lowest IC50 value. In addition, compounds 10a and 10b showed high scavenging activity. The compounds 9a (A375: IC50 = 34.7 ± 0.9 µg/mL and MDA-MB-231: IC50 = 20.4 ± 1.1 µg/mL), 10a (A375: IC50 = 19.6 ± 1.3 µg/mL and MDA-MB-231: IC50 = 37.0 ± 1.3 µg/mL) and 10b (A375: IC50 = 16.5 ± 1.5 µg/mL and MDA-MB-231: IC50 = 13.4 ± 1.5 µg/mL) showed the significant cytotoxicity against these human cancer cell lines (melanoma and breast cancer) and can be potential anti-cancer molecules.